Erectile Dysfunction in 45-Year-Old Heterosexual German Men and Associated Lifestyle Risk Factors and Comorbidities: Results from the German Male Sex Study. Issue 1 (9th January 2019) - Hallanzy, Jacqueline; Kron, Martina; Goethe, Veronika E.; Köhn, Frank-Michael; Schmautz, Maximilian; Arsov, Christian; Hadaschik, Boris; Imkamp, Florian; Gschwend, Jürgen E.; Herkommer, Kathleen
Abstract: Background: Erectile dysfunction (ED) is a common public health issue with a significant impact on quality of life. The associations between ED and several risk factors have been reported previously. The continuously increasing incidence of these factors is contributing to the increasing prevalence of ED. Aim: To assess ED prevalence and severity in a representative sample of 45-year-old German men and to analyze the association with risk factors (lifestyle risk factors/comorbidities). Methods: Data were collected within the German Male Sex-Study. Randomly selected 45-year-old men were invited. A total of 10, 135 Caucasian, heterosexual, sexually active men were included in this analysis. The self-reported prevalence of ED was assessed using the Erectile Function domain of the International Index of Erectile Function. Risk factors for ED were ascertained using self-report questionnaires. An anamnesis interview and a short physical examination were performed. Main Outcome Measure: ED prevalence and severity were evaluated in a cross-sectional design. The associations of ED with comorbidities (eg, depression, diabetes, hypertension, lower urinary tract symptoms) and lifestyle factors (ie, smoking, obesity, central obesity, physical inactivity, and poor self-perceived health-status) were analyzed by logistic regression. Results: The overall prevalence of ED was 25.2% (severe, 3.1%; moderate, 9.2%; mild to moderate, 4.2%; mild, 8.7%). Among the men with ED, 48.8% had moderate or severe symptoms. ED prevalence increased with the number of risk factors, to as high as 68.7% in men with 5–8 risk factors. In multiple logistic regression with backward elimination, the strongest associations with ED were found for depression (odds ratio [OR] = 1.87), poor self-perceived health status (OR = 1.72), lower urinary tract symptoms (OR = 1.68), and diabetes (OR = 1.38). Conclusion: One out of 4 men already had symptoms of ED at age 45. Almost one-half of the men with ED had moderate to severe symptoms. ED was strongly associated with each analyzed risk factor, and the prevalence and severity of ED increased with an increasing number of risk factors.